Avaliação retrospectiva do perfil clínico de pacientes acometidas com câncer de mama e diabetes mellitus tipo 2 - Ricarte, Valter Augusto Souza (2024)
Breast cancer is the most prevalent type among women globally and in Brazil. Various studies have investigated the correlation between different risk factors in the development and progression of this cancer, including Diabetes Mellitus. This retrospective epidemiological study analyzed the influence of Type 2 Diabetes Mellitus (DM2) and metformin, a drug widely used in its treatment, on the outcomes of 213 patients with breast cancer treated at the Hospital de Clinicas of the Federal University of Uberlândia. Survival outcomes were compared between diabetic and non-diabetic patients. The average age at breast cancer diagnosis was 59.7 years for the diabetic group and 63.9 years for the non-diabetic group. Overall survival for diabetic and non-diabetic patients was 30.7 and 22.9 months, respectively, with a mean overall survival of 26.5 months (95% CI). The diabetic group showed significantly greater survival compared to the non-diabetic group when considering patients who had advanced tumors or were diagnosed with invasive carcinomas at the time of diagnosis. The presence of DM2 did not have a significant positive or negative impact on prognosis during the analyzed period. However, the continuous use of metformin resulted in a significant increase in survival for these patients.